(untitled) (Journal of Bangladesh Academy of Sciences, 2026)
Andharmanik river system (ARS), a Hilsa sanctuary on the southern coast of Bangladesh, is a critical ecological zone supporting fisheries biodiversity and local livelihoods. However, increasing anthropogenic pressures in the surrounding coastal region have heightened concerns regarding heavy metal (HM) contamination and associated ecological risks. Hence, the present study aimed to measure HM concentrations in the surface water (SW) of ARS using Inductively Coupled Plasma Mass Spectrometry method, assess the spatial distribution and evaluate their ecological risk, where samples were collected from 10 stations during the winter season of 2024 positioned by Global Positioning System (GPS). The average concentration of HMs followed the order: Zn (1.41) ˃ Ni (0.09) ˃ Pb (0.07) ˃ Cr (0.052) ˃ Cu (0.046) ˃ Mn (0.019) ˃ As (0.008) ˃ Cd (0.0005) ˃ Hg (0.00001) in mg/L; notably, Pb, As, Cr and Ni being considered as the major contaminants under the Bangladesh Environment Conservation Rules (ECR) 2023. Sources of HMs were estimated by principal component analysis (PCA) and hierarchical cluster analysis (HCA), along with Pearson correlation. Multiple indices were used to assess HM contamination status and the results showed a low to moderate contamination. The findings highlight an increasing environmental stress on this protected river system and underscore the importance of long-term monitoring and sustainable management strategies to safeguard the ecological health of ARS and its vital Hilsa habitat. J. Bangladesh Acad. Sci. 50(2); 233–246: June 2026